Methylglyoxal and Advanced Glycation End Products in Patients with Diabetes – What We Know so Far and the Missing Links - Groener, Jan Benedikt; Oikonomou, Dimitrios; Cheko, Ruan; Kender, Zoltan; Zemva, Johanna; Kihm, Lars; Muckenthaler, Martina; Peters, Verena; Fleming, Thomas; Kopf, Stefan; Nawroth, Peter P. (Experimental and Clinical Endocrinology & Diabetes, 2019)
Hyperglycemia explains the development of late diabetic complications in patients with diabetes type 1 and type 2 only partially. Most therapeutic efforts relying on intensive glucose control failed to decrease the absolute risk for complications by more than 10%, especially in patients with diabetes type 2. Therefore, alternative pathophysiological pathways have to be examined, in order to develop more individualized treatment options for patients with diabetes in the future. One such pathway might be the metabolism of dicarbonyls, among them methylglyoxal and the accumulation of advanced glycation end products. Here we review currently available epidemiological data on dicarbonyls and AGEs in association with human diabetes type 1 and type 2.
Keywords: AGE; human; complications; retinopathy; nephropathy; neuropathy